36. Testicular histopathology of mice (Mus musculus) which have been exposed to cigarette smoke and given red watermelon extract (Citrullus vulgaris) - Ayu Agita Ginting; Ummu Balqis; Hamny Hamny; Cut Dahlia Iskandar; Zainuddin Zainuddin; T. Armansyah; Fitriani Fitriani (Universitas Syiah Kuala, 2019)
This research aims to know the testicular histopathology of mice that have been exposed to cigarette smoke and given red watermelon extract dosage 22 mg and 44 mg. Experimental research using completely random design (RAL) with 4 group treatments. The negative control group (KN). The positive control group (KP) which have been exposed to cigarette smoke. Treatment group 1 (K1) which have been exposed to cigarette smoke and given the red watermelon extract 22 mg. Treatment group 2 (K2) which have been exposed to cigarette smoke and given the red watermelon extract 44 mg. Exposed to cigarette smoke conducted in the morning for an hour to burn one cigarette and red watermelon extract given in the afternoon. This was done for 30 days. On day 31, mice were sacrificed and their testis were taken to weighed and made histology slide. The data were analyzed using ANOVA in one direction and continued with Duncan. The results of this research showed that the extract of red watermelon for 30 days looks a highly significant effect (P 0.05) to the diameter of the seminiferous tubules, the number of spermatogonia cells, primary spermatocytes cells, spermatid cells. While on the weight of the testes showed no real effect (P 0.05). Red watermelon extract dosage 22 mg dan 44 mg of the mice exposed cigarette smoke can prevent cell damage in mice testis.